ANALISIS SISTEM PEGENDALIAN INTERN TERHADAP PENGGAJIAN PADA TOSERBA SINAR MAS ENDE - A, M Samsul; Thalib, Sabra B Wahab; Soleiman, Iriany Dewi (Program Studi Akuntansi Universitas Flores, 2020)
The purpose of this study was to determine the payroll information system in Sinar Mas Ende Department Store. The data analysis technique used is descriptive by using a qualitative approach, where the data collected takes the form of words and pictures rather than numbers. The results of the analysis of the internal control system on payroll at the Sinar Mas Ende Department Store show that there are weaknesses caused by the double duty manager and manual attendance record that has the potential to cause irregularities. Companies are advised to add one more function, namely the financial function and use fingerscan to record employee attendance lists.